Ekonomi Lokal dan Pembangunan Pedesaan di Dusun Berambai, Kalimantan Timur - Arman Arman; Asep Saefuddin (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
The role of the local economy gets eroded due to the inclusion of capitalization in rural areas. This research examines the coal mining industry's influence on the local economy's existence in Berambai Hamlet, Bukit Pariaman Village, Tenggarong Seberang Sub-district, Kutai Kartanegara Regency, East Kalimantan Province, Indonesia. This research uses qualitative research methods; meanwhile, data collection methods use field observation and in-depth interviews. Interviews were conducted in stages through a snowball sampling to strengthen the observations' results. The results show that the local economy and livelihood in Berambai Hamlet are under pressure and eroded due to coal mining activities. Livelihood products shrank drastically, especially fish and rice, due to mining waste polluting rivers and agricultural land conversion to mining areas. Furthermore, other sources of income from farmworkers are not enough to fulfill the needs. The government needs to protect their livelihoods as a driving force for the local economy by integrating nature-based life. The government needs to develop local economic potentials, such as tourism areas, crafts, and artworks. The government also needs to strengthen village institutions. It must be carried out together with mining companies seriously. Furthermore, the government needs to maintain the unity of rural spatial and spatial planning.